New Straits Times, 24 September 2008 (The New Straits Times Press (M) Bhd, 2008)
The report "20,000ha gazetted for Orang Asli reserve" (New Sunday Times, Sept 21) and the accompanying stories suggest that the Department of Orang Asli Affairs is going on a campaign to promote itself as the godfather of the Orang Asli.